Verräter? Vorbilder? Verbrecher? Kontroverse Deutungen des 20. Juli 1944 seit 1945 - Brechtken, Magnus 1964- VerfasserIn; Cornelißen, Christoph 1958- VerfasserIn; Dowe, Christopher 1973- VerfasserIn; Hecht, Cornelia 1968- VerfasserIn; Knoch, Habbo 1969- VerfasserIn; Kroener, Bernhard 1948- VerfasserIn; Searle, Alaric 1962- VerfasserIn; Haus der Geschichte Baden-Württemberg; Frank & Timme; Tagung im Haus der Geschichte Baden-Württemberg zur Rezeptionsgeschichte des 20. Juli 1944 (Geschichtswissenschaft, 2016)
Since the collapse of the Hitler regime, many have tried to enforce their respective image of the coup attempt of July 20, 1944 in public. In this work, well-known experts from Germany and abroad show how controversial the interpretations of the coup attempt of July 20 were in the Federal Republic.